2015
DOI: 10.5539/ijms.v7n2p70
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Country of Origin and Country of Manufacture of a Brand on Overall Brand Equity

Abstract: The main purpose of this study is to explore the effects of country-of-origin of a brand (COB) and country of manufacture (COM) on the overall brand equity (OBE). A second purpose of this research is to investigate the mediating role of consumer based brand equity (CBBE) on the relationship between COB and COM and overall brand equity (OBE). To undertake this, a conceptual framework was designed and relationships among its constructs COB, COM, CBBE, and OBE were hypothesized. Data were collected from consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 63 publications
4
21
0
5
Order By: Relevance
“…Country of Origin (COO) image has a major role in how consumers are forming their relationship with a foreign brand; particularly it has a critical impact on consumers' perception of product quality thereby affecting their choice of a particular brand. Regarding the effects of the COO in the CBBE, findings in this study are supported by previous studies (Murtiasih et al, 2013 andMostafa, 2015;Fischer et al, 2012;Knight and Calantone, 2000). Various studies validate the relationship between COO and CBBE.…”
Section: Renee B Kim Yan Chaosupporting
confidence: 91%
“…Country of Origin (COO) image has a major role in how consumers are forming their relationship with a foreign brand; particularly it has a critical impact on consumers' perception of product quality thereby affecting their choice of a particular brand. Regarding the effects of the COO in the CBBE, findings in this study are supported by previous studies (Murtiasih et al, 2013 andMostafa, 2015;Fischer et al, 2012;Knight and Calantone, 2000). Various studies validate the relationship between COO and CBBE.…”
Section: Renee B Kim Yan Chaosupporting
confidence: 91%
“…Similarly, H2 showed that brand awareness (0.159) has a positive influence on brand equity. This result is consistent with previous studies by Taleghani & Almasi (2011);Mohan & Sequeira, (2012); Ahmad & Sherwani (2015); Mostafa (2015). The finding points out that Heineken should continue to strengthen brand awareness because the more familiar and more easily identifiable by consumers, the more likely Heineken will be engraved in the consumer's perception.…”
Section: Managerial Implicationssupporting
confidence: 83%
“…In addition, many empirical evidences from researches (e.g. Taleghani & Almasi, 2011;Mohan & Sequeira, 2012;Ahmad & Sherwani, 2015;Mostafa, 2015) supported the positive relationships between brand awareness and brand equity. Thus, the following hypothesis is formulated:…”
Section: Effect Of Brand Awareness On Brand Equitymentioning
confidence: 99%
See 1 more Smart Citation
“…This notion has been termed as 'brand equity', and such strong brand has become as a firm's most valuable asset due to the positive consequences on the firm's performance (Aaker, 1991;Tuominen, 1999). Therefore, the brand equity concept has received significant attention in the marketing literature (Kim et al, 2008;Mostafa, 2015). However, the definition of brand equity was basically relied on two different aspects, the financial aspect (financial-based brand equity) and the customer aspect (customer-based brand equity) (Aaker, 1991;Chang et al, 2008).…”
Section: Brand Equitymentioning
confidence: 99%